The Impact of the Training Mode on Students” Performance - Adaskina A.A.; Meluhina N.A. (Психолого-педагогические исследования, 2020)
The article presents the results of a study of the influence of the training regime on the subjective characteristics of working capacity (well-being, activity, mood), as well as on the number of absenteeism classes during the school year by students in grades 5–6. Currently, two training modes are used in the Russian Federation: traditional (4 quarters separated by autumn, winter and spring breaks) and modular (consisting of 6 intervals of 5-6 weeks separated by weekly breaks). The study involved students of grades 5-6 (152 students), parents (128 people) and teachers (25 people). The study was conducted using a specially designed questionnaire, which includes three blocks. An analysis of the attendance of students in two Moscow schools was conducted. In the course of the study, the following results were obtained: in the modular mode of instruction, by the end of the school year, students feel more active and are in a good mood. In the traditional mode of instruction, students feel more tired by the end of the school year. Signs of fatigue are observed. Statistically significant differences were obtained when analyzing the responses of students and teachers. In the traditional mode of training, the number of missed classes and the number of frequently ill children is significantly higher than in the modular mode. The modular mode, based on a uniformly distributed load, according to subjective assessments of students in grades 5-6, teachers and parents is more preferable to maintain performance.